Integrated hydro informatics tool to assess hydrological alteration on gauged sites: Hydra-Eflow. (February 2023) - Arévalo-Mejía, Ricardo; Leblois, Étienne; Mastachi-Loza, Carlos Alberto; Salinas-Tapia, Humberto; Bâ, Khalidou M.; Vilchis-Francés, Aleida Yadira; Becerril-Piña, Rocío; Díaz-Delgado, Carlos
Abstract: The alterations in the hydrosphere dynamics are undeniable. However, the analysis of hydrological alterations provides a benchmark to identify the potential environmental consequences and triggers of the evinced deviations. Hydra-Eflow is a free download and integrated hydro-informatics tool to assess gauged site discharge timeseries deviations for two non-concomitant samples through the Hydrologic Alteration Indices on Rivers (IAHRIS, acronym in Spanish). Its modules allow data quality verification, traditional frequency analysis, alteration analysis, and desktop environmental flow prescription. In addition, Hydra-Eflow supplies recommendations by an expert-based adjacency matrix to guide forward cascading studies and provide helpful rules for robust models. A case study at the Balsas River Basin is shown to verify the consistency of the information generated by Hydra-Eflow. Results show that 96 out of 129 hydrometric stations are altered due to changes in the discharge regime derived from the densified number of dams and impoundments in the streams for a wide range of purposes. Furthermore, the middle northern sub-basins exhibit a high alteration degree which may cause appalling water resources management since they submit more than 25% of the drinking water consumed in Mexico City. Finally, Hydra-Eflow supplied information to improve the heuristics of hydrologic alteration in the Balsas River Basin. Graphical abstract: Image 1 Highlights: Hydra-Eflow is a friendly tool for an insightful hydrological alteration analysis. Hydra-Eflow provides recommendations that follow expert heuristics. The Balsas River Basin showed significant hydrologic alterations in the regime. Alterations are more severe in the lower sub-basins due to flow depletion. Structured system analysis showed consistent alteration dynamics.